EVOLUŢIA FINANŢELOR PUBLICE ÎN EPOCA MODERNĂ - Grincu, Olesi (CEP USM, 2009)
The evolution of public finances to the form that is known and usual in our days was performed during last three centuries and was characterised by a strong and wealthy base in XVIII-th and XIX-th centuries, but many economic crises had appeared, also as well as total wars, that had affected globally and turned off many principles of budgeting, collection of taxes, also the redistribution of them.
Keywords: finanţe publice; finanţe